2016
DOI: 10.1002/adma.201601369
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Visible Quasi‐2D Perovskite Light‐Emitting Diodes

Abstract: Efficient quasi-2D-structure perovskite light-emitting diodes (4.90 cd A(-1) ) are demonstrated by mixing a 3D-structured perovskite material (methyl ammonium lead bromide) and a 2D-structured perovskite material (phenylethyl ammonium lead bromide), which can be ascribed to better film uniformity, enhanced exciton confinement, and reduced trap density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
584
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 597 publications
(596 citation statements)
references
References 27 publications
11
584
0
1
Order By: Relevance
“…However, these devices show low efficiency (below 1%) and limited photo-stability ( Table 1) 23,24 .…”
mentioning
confidence: 99%
“…However, these devices show low efficiency (below 1%) and limited photo-stability ( Table 1) 23,24 .…”
mentioning
confidence: 99%
“…Practically, a mixture of small and large organic cations is applied to the perovskite structure. In most cases, quasi 2D "Ruddlesden-Popper (RP)" phase PNCs were reported, [56,[63][64][65][66] which can be treated as a mixture of multilayered PNCs while nanosized 3D PNCs were reported elsewhere. [55] Here, the selection and incorporation concentration of bulky organic cations, the controlling of spin-coating process as well as the antisolvent play an important role in the formation mechanism.…”
Section: The Roadmap Of Perovskite Nanocrystalsmentioning
confidence: 99%
“…As mentioned above, the quasi 2D PNC structure can be denoted as L 2 A n−1 B n X 3n+1 . Plenty of investigations have been conducted on the choices of bulky cation L, including PEA, [56,63,64,[89][90][91][92] BA, [55,88,[93][94][95] ethylammonium (EA), [96] phenylmethylamine (PMA), [97] phenylbutylammonium (PBA), [98,99] naphthylmethylamine (NMA) [65,100] and 2-Phenoxyethylamine (POEA). [101] Similar to the pure 2D structure, with the space dimension reduced to nanosized 3D or quasi 2D, the PNCs exhibit strong excitonic behavior.…”
Section: Organic Ammonium Assisted In Situ Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…These works demonstrated that pure perovskites can emit bright EL with very high color purity at RT. Many subsequent studies used a variety of experimental approaches to improve the luminescence efficiencies of PeLEDs (8)(9)(10)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66).…”
Section: Renaissance Of Perovskite Emitters: Bulk Polycrystalline Filmentioning
confidence: 99%